Efektivitas Pemberdayaan Masyarakat Melalui Dana Desa di Kabupaten Lampung Barat - Zumaroh Zumaroh (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2019)
This research began with a community empowerment program launched through the Village Funds Budget. Community empowerment is the lowest priority in managing village funds after development and government. In fact, empowerment that currently does not reach 30% of the village funds budget can create a more independent community. However, until now the independence of the community has not been realized to its full potential. By using a socio-empirical research and program evaluation approach, it is expected that this research can obtain a real picture of the effectiveness of community empowerment through village funds in West Lampung. The community empowerment program launched by the government through the management of village funds in West Lampung is still not effective. This is caused by several factors, namely: the level of geographical difficulties of Pekon in the mountainous region, and the relatively low level of education of the community and Pekon apparatus. These causes make empowerment when viewed in terms of the programs offered are very good. However, the implementation is still not effective where the village funds management apparatus lacks the courage to develop the program on the grounds that there are no official technical guidelines from the regional government.